Analisis Pengaruh Stres Kerja, Kompensasi, dan Lingkungan Kerja terhadap Turnover Intention (Studi Kasus pada PT. Sukses Ekspor Indonesia) - Musyaffa, Muhammad Faris; Mansur, Mochammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the effect of job stress, compensation, and work environment on turnover intention among employees of PT. Sukses Ekspor Indonesia. The study employs a quantitative approach using a causal method. Data were collected through the distribution of questionnaires to all employees of PT. Sukses Ekspor Indonesia, totaling 37 respondents, using a saturated sampling technique. The data were analyzed using multiple linear regression with SPSS 27 as the analytical tool. The results indicate that job stress has a positive and significant effect on turnover intention, meaning that the higher the level of job stress experienced by employees, the greater their tendency to leave the company. Compensation has a negative and significant effect on turnover intention, indicating that fair and adequate compensation can reduce employees’ intention to leave the company. In addition, the work environment also has a negative and significant effect on turnover intention. Based on these findings, companies are expected to manage job stress more effectively, improve compensation systems, and create a more conducive work environment to reduce employees’ turnover intention.